PENERAPAN TATA KELOLA PERUSAHAAN YANG BAIK (Good Corporate Governance) DI BIDANG PENGAMANAN ASSET UNTUK MEMINIMALISIR PENCURIAN TANDAN BUAH SEGAR (TBS) KELAPA SAWIT DI PTPN IV - Junaedi Junaedi (Res Nullius Law Journal, 2020)
on the contrary, good employees must also have a sense of belonging and high loyalty to the company where they work. PT. Perkebunan Nusantara IV (Persero) is a State-Owned Enterprise (SOE) in the form of a Limited Liability Company (PT) (hereinafter referred to as PTPN IV). In the context of state-owned PT, a good state-owned PT is a state-owned PT that can contribute to stakeholders to ensure public welfare. The instrument for PTPN IV to contribute to stakeholders in order to ensure the realization of public welfare is the implementation of Good Corporate Governance (GCG). In addition, in implementing GCG it is also necessary to apply Good Corporate Culture (GCC) because GCG and GCC have a very close relationship. GCG is the visible side of the company, while the GCC is the inside side of the company or the value side of corporate management. Assets with a total value of more than Rp. 14 trillion must be secured for the sustainability and sustainability of the company's business wheels. The safeguarding of these assets must start from the smallest, an example in this study is the security of oil palm Fresh Fruit Bunches (FFB) which are often stolen, both by â€œninjaâ€, and â€œmafiasâ€. Various modes of crime surfaced, such as theft of FFB; trimming FFB; land grabbing; employee abuse; darkening of the core & Crude Palm Oil (CPO); and employee mistreatment. One of the breakthroughs in implementing GCG that will be implemented at PTPN IV to secure assets to minimize the theft of oil palm FFB is the application of technology, information, and communication at PTPN IV in the form of an application system "Smart Security of Integrity". Keywords. Good Corporate Governance; Asset Security; and PTPN IV Palm Oil Theft